2022
DOI: 10.3991/ijep.v12i1.27603
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Design-Based Learning Management Model to Promote Thai Undergraduate Computational Thinking Skills and Programming Proficiency

Abstract: The study applied concepts of computational thinking, waterfall programming, and design-based learning management (DBLM) combined with a participatory action research (PAR) methodology to obtain an integrated learning management model (LMM) designed as a base to promote computational thinking skills (CTS) and programming proficiency. The study used three groups consisting of 21 volunteer computer science undergraduate students, three teachers, and three computer studies graduates from the Computer Studies Depa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The Research Ethics Committee at the authors' university certified that the study complied with the Helsinki Declaration's international guidelines for human research protection. Furthermore, all study participants were notified of the confidentiality of their information [ [60] , [61] , [62] , [63] ]. The Principal Investigator Name Study code assigned was EC-KMITL_66_006, dated November 20, 2022.…”
Section: Methodsmentioning
confidence: 99%
“…The Research Ethics Committee at the authors' university certified that the study complied with the Helsinki Declaration's international guidelines for human research protection. Furthermore, all study participants were notified of the confidentiality of their information [ [60] , [61] , [62] , [63] ]. The Principal Investigator Name Study code assigned was EC-KMITL_66_006, dated November 20, 2022.…”
Section: Methodsmentioning
confidence: 99%
“…CompThink skills and programming skills have been referred to as necessary skills for digitally enabled knowledge workers in a 21 st economy [15], [16]. CompThink has also been stated to be basic in analyzing, solving problems, designing workflows, and understanding human behavior [17].…”
Section: Computational Thinking (Compthink)mentioning
confidence: 99%
“…Research has shown that using a participatory action research (P.A.R.) methodology allows participation from beginning to end [59], [60]. Under P.A.R.…”
Section: The Cpss Training Course Development Using Digital Storytell...mentioning
confidence: 99%